Investigation of the Relationship Between Impulsivity and Night Eating Attitudes of Obese and Nonobese Individuals - Uncu, Fatos; Evcimen, Hasan; Gulnaroglu, Betul (Mary Ann Liebert, Inc, 2020)
Purpose: The purpose of this study is to examine the relationship between impulsivity and night eating attitudes of obese and nonobese individuals. Method: This case-control study was conducted between 90 obese people who applied for bariatric surgery to the General Surgery Clinic of a university hospital and 87 nonobese people matched to obese people by age and gender in the same clinic. Ethical permission was obtained from the Firat University Noninvasive Ethics Committee. The Barratt's Impulsiveness Scale (BIS), Night Eating Questionnaire (NEQ), and a questionnaire examining the sociodemographic characteristics of people, such as age, gender, marital status, height, and weight, were used to collect data. Findings: Regarding BIS scores between obese and nonobese individuals; there was a significant difference between BIS total, BIS inattention, BIS motor impulsivity, and BIS nonplanning impulsivity (p<0.05). The mean NEQ score of obese people (28.86.8) was significantly higher than the nonobese NEQ scores (22.4 +/- 16.3) (p<0.05). There was a statistically significant relationship between NEQ and BIS in the positive direction (p<0.05). Results: It was determined that high impulsivity level and night eating are important factors in the development of obesity. We think that further research is needed on the basis of impulsivity and night eating attitude on obese people.
Keywords: obesity; impulsivity; night eating attitude